2021
DOI: 10.1186/s12879-021-06088-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of renin–angiotensin–aldosterone system inhibitors with other antihypertensives in association with coronavirus disease-19 clinical outcomes

Abstract: Background Reports on the effects of renin–angiotensin–aldosterone system (RAAS) inhibitors on the clinical outcomes of coronavirus disease-19 (COVID-19) have been conflicting. We performed this meta-analysis to find conclusive evidence. Methods We searched published articles through PubMed, EMBASE and medRxiv from 5 January 2020 to 3 August 2020. Studies that reported clinical outcomes of patients with COVID-19, stratified by the class of antihype… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Large meta-analyses have shown that neither RAAS, nor other antihypertensive drugs, nor NSAIDs are associated with increased risk of death. The reason for previous observations was not the influence of drugs on COVID-19, but it was the effect of underlying comorbidities alone [19,20]. Moreover, statins, due to their anti-inflammatory effect, are associated with lower risk of fatal COVID-19 [21][22][23] among non-ICU patients and lower risk of mechanical ventilation treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Large meta-analyses have shown that neither RAAS, nor other antihypertensive drugs, nor NSAIDs are associated with increased risk of death. The reason for previous observations was not the influence of drugs on COVID-19, but it was the effect of underlying comorbidities alone [19,20]. Moreover, statins, due to their anti-inflammatory effect, are associated with lower risk of fatal COVID-19 [21][22][23] among non-ICU patients and lower risk of mechanical ventilation treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…This study was not the first systematic review and meta‐analysis to assess the associations between RAAS inhibitor use and COVID‐19 outcomes. As of December 2021, at least 52 meta‐analyses had been conducted, 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 each of which pooled studies that have a critical risk of bias. Critical biases limit confidence in the evidence produced by these meta‐analyses as much as they do in each of the studies that t...…”
Section: Discussionmentioning
confidence: 99%
“… 6 At least 52 meta‐analyses have assessed associations between RAAS inhibitor use and COVID‐19 risk by collating parts of that body of research. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 However, little attention has been paid to selection bias, or other biases for that matter, which may distort the interaction between RAAS inhibitor use and COVID‐19.…”
mentioning
confidence: 99%
“…al. 11 , though they report no overall direct impact of RAAS inhibitors distinct from the comorbidities. In our study we show there is a distinct interaction of RAAS drugs with the impact of hypertension on severe C19.…”
Section: Discussionmentioning
confidence: 97%
“…The role RAAS plays in hypertension (HT) makes RAAS an important target of HT drugs. [7][8][9][10][11] Differences in HT severity 12 and responsiveness to treatment modalities [12][13][14][15][16] are associated with race and represented in current standard Clinical Practice Guidelines. 16 How C19 affects RAAS among African Americans may offer more insight into how hypertension is expressed in this population.…”
Section: Introductionmentioning
confidence: 99%